O gênero discursivo digital podcast aplicado à educação: pressupostos teóricos e práticos. - Lottermann, Gabriel Fischer (2022)
This study investigates the applicability of the podcast, digital discursive genre, cited in the Base Nacional Comum Curricular – BNCC, to the teaching of the Portuguese Language – LP. It assumes, as a thematic delimitation, reflections on theoretical and practical specifications of the comparison of discursive genres, in particular the podcast genre, in LP classes in High School, in order to serve as a basis for teaching reflection and as one of the possible ways to work digital genres in basic and public education. In this context, the question that guides the research is: to what extent does the study of the constitutive and organizational nature of the digital podcast discursive genre help for the formation in the perspective of Multiletramentos in High School? Indeed, the general objective is to reflect on the digital podcast discursive genre from the perspective of Multiletramentos. As a theoretical contribution, for the didactic proposal to be presented, the methodology of the Plano de Trabalho Docente – PTD – by Gasparin (2007) is selected, the result of the author's research in the areas of Pedagogia Histórico-Crítica, by Saviani (2008), and Teoria Dialética do Conhecimento. In turn, the theoretical perspectives selected for approaching the syllabus are based on the Estudos Dialógicos of the Bakhtin Circle (BAKHTIN, 2003[1952-1963]; 2016; VÓLOCHINOV, 2021[1929]; MEDVIÉDEV, 2012 [1928]) , in the theory of Multiletramentos (NEW LONDON GROUP, 1996; ROJO, 2013; ROJO; MOURA, 2013; 2019; ROJO; BARBOSA, 2015), as well as in analyzes of the podcast genre for the construction of the proposal. The methodology of this investigation fits into the area of Linguística Aplicada – LA – and has a qualitative approach with an interpretive nature of the data. The research is carried out by indirect documents, with a bibliographic review and production of didactic-pedagogical material for working with the podcast genre, applicable to High School and, therefore, assumes a propositional character. Indeed, it is Pesquisa-ação (ENGEL, 2000), with regard to the first two aspects of this type of investigation. As a result, it is believed that the questions raised here contribute to the teacher's reflection on the use of digital technologies applied to education and the comparison of digital discursive genres. In this sense, it is consistent with hypermodernity, in which social practices are mediated by textos-enunciados that also circulate in digital media.